2023
DOI: 10.3389/fphar.2023.1128924
|View full text |Cite
|
Sign up to set email alerts
|

S-Ketamine attenuates inflammatory effect and modulates the immune response in patients undergoing modified radical mastectomy: A prospective randomized controlled trial

Abstract: Objective: This study aimed to investigate the impact of varying dosages of S-ketamine on perioperative immune-inflammatory responses in patients undergoing modified radical mastectomy (MRM).Methods: This is a prospective, randomized, controlled trial. A total of 136 patients with American Society of Anesthesiologists status I/II scheduled for MRM were enrolled and randomly assigned into groups to receive the control (C) or one of three different doses [0.25 (L-Sk), 0.5 (M-Sk), or 0.75 (H-Sk) mg/kg] of S-ketam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Anesthesia with continuous infusion of esketamine after a single intravenous injection during elective coronary artery bypass graft (CABG) surgery decreases plasma proin ammatory cytokines (IL-6 and IL-8) and increases plasma IL-10 during and after cardiopulmonary bypass (26). Combined use of esketamine for induction and maintenance could also exert a systemic anti-in ammatory effects, and increase the absolute counts of CD3 + and CD4 + cells in patients at the end of and 24 h after modi ed radical mastectomy (27). Our present study further revealed potential anti-in ammatory effects of esketamine on secondary infectioninduced systemic in ammation and elucidated the mechanism of its anti-in ammatory effects by attenuating the downregulation of hippocampal BDNF through inhibiting the intestinal ora/subdiaphragmatic vagus nerve/spleen axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anesthesia with continuous infusion of esketamine after a single intravenous injection during elective coronary artery bypass graft (CABG) surgery decreases plasma proin ammatory cytokines (IL-6 and IL-8) and increases plasma IL-10 during and after cardiopulmonary bypass (26). Combined use of esketamine for induction and maintenance could also exert a systemic anti-in ammatory effects, and increase the absolute counts of CD3 + and CD4 + cells in patients at the end of and 24 h after modi ed radical mastectomy (27). Our present study further revealed potential anti-in ammatory effects of esketamine on secondary infectioninduced systemic in ammation and elucidated the mechanism of its anti-in ammatory effects by attenuating the downregulation of hippocampal BDNF through inhibiting the intestinal ora/subdiaphragmatic vagus nerve/spleen axis.…”
Section: Discussionmentioning
confidence: 99%
“…(R)-Ketamine is well established to exert protective effects in a variety of in ammatory diseases, including LPS-induced depression-like behaviors (21), ischaemic stroke (22), Parkinson's disease (23), and ulcerative colitis (24). Complementarily, esketamine also possesses antiin ammatory properties (25)(26)(27). Nonetheless, it remains unclear whether esketamine alleviates systemic in ammation and cognitive dysfunction in secondary LPS exposure-imitating secondary infection postrecovery from primary LPS injection-mediated endotoxaemia.…”
Section: Introductionmentioning
confidence: 99%
“…A recent randomized controlled trial assessed the impact of three distinct doses of s-ketamine (0.25, 0.5, and 0.75 mg/kg at induction, followed by infusions of 0.25, 0.5, and 0.75 mg/kg/h, respectively) on immune-inflammatory function in patients undergoing modified radical mastectomy [92]. The data indicated that s-ketamine doses of 0.5 mg/kg and 0.75 mg/kg had a diminished impact on patients' cell-mediated immune function, resulting in a more attenuated inflammatory response.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Esketamine, the s-enantiomer of ketamine, has more potent analgesic and sedative effects, particularly favorable sympathomimetic properties, with fewer adverse reactions than racemic ketamine [6,7]. It is now a popular medicine that is widely used in various areas [8], helps decrease propofol dosage, reduces the incidence of respiratory depression, stabilizes hemodynamics [9][10][11], and improves postoperative recovery quality [12][13][14]. Nevertheless, studies examining the e cacy and safety of the combination of esketamine and propofol for curative colorectal endoscopic resection are lacking.…”
Section: Introductionmentioning
confidence: 99%